Residual dynamic and risk assessment of dimethomorph in Swiss chard grown at two different sites. (28th August 2017) - Kabir, Md. Humayun; Abd El‐Aty, A. M.; Rahman, Md. Musfiqur; Chung, Hyung Suk; Lee, Han Sol; Kim, Mi‐Ra; Chang, Byung‐Joon; Wang, Jing; Shin, Ho‐Chul; Shim, Jae‐Han
Abstract: Residue analysis of dimethomorph in Swiss chard cultivated at two different locations under greenhouse conditions was conducted using high‐performance liquid chromatography–ultraviolet detection and confirmed by tandem mass spectrometry. The randomly collected samples (over 14 days) were extracted with acetonitrile and purified using a Florisil solid‐phase extraction cartridge. Linearity over a concentration range of 0.05–50.0 mg/L had an excellent coefficient of determination of 0.9996. Recovery rate ranged from 82.98 to 95.43% with relative standard deviations ≤5.12% and limits of detection and quantification of 0.003 and 0.01 mg/kg, respectively. The initial deposits [day 0 (2 h post‐application)] were considerably lower (7.57 and 8.55 mg/kg for sites 1 and 2, respectively) than the maximum residue limit (30 mg/kg) set by the Korean Ministry of Food and Drug Safety. The dissipation half‐life was approximately the same, being 5.0 and 5.1 days for sites 1 and 2, respectively. Risk assessment estimated as acceptable daily intake revealed a value of 0.084 or 0.094% (day 0) and 0.014% (10 days post‐application), for sites 1 and 2, respectively. The values indicated that dimethomorph can be safely used on Swiss chard, with no hazardous effects expected for Korean consumers.